PRINCIPAL'S LEADERSHIP IN REALIZING CHARACTER EDUCATION - Sutino sutino; Sowiyah sowiyah; Novita Eka Tristiana (Universitas Ahmad Dahlan, 2021)
The Important of the principal's leadership in implementing a character education program attracts the author to conduct research and this article discusses the results of a literature review conducted by the author. There are a number of articles on the review of principals' leadership and character education especially in the world context that can be found. The purpose of this review is to find out the principal's leadership in realizing character education in a world context. Based on the results of the literature reviews from various countries in the world, the authors find the scope of the article being reviewed is still very limited and it is very difficult to get literature that combines the two variables. The results of the literature review about the principal's leadership show that the principal's leadership in carrying out his role as a leader has an impact on teacher performance and student personality. Literature review of character education shows that the principal has a big role in realizing students' personalities. Thus, the authors are interested in following up related to the principal's leadership in realizing character education.